Hyperthermia and the generation and activity of murine influenza-immune cytotoxic T cells in vitro. - Müllbacher, A (1984)
The rate of generation of murine secondary influenza virus-immune cytotoxic T cells in vitro is enhanced under limiting dilution conditions at hyperthermal temperatures (39 versus 37 degrees C). Increased mean values of cytotoxic activity were observed in the presence as well as absence of exogenous helper factors. Elevated cytotoxic activity at 39 degrees C was observed after day 3 to day 5 of culture. The number of autoreactive cytotoxic cells observed was not greater at 39 degrees C than at 37 degrees C. Elevated temperature did not influence target cell lysis or release of isotopes from killed target cells. The results are discussed with a view to the role of fever in augmenting the cellular immune response responsible for the host defense against primary viral infection.